Mapping the rat gastric slow-wave conduction pathway: bridging in vitro and in vivo methods, revealing a loosely coupled region in the distal stomach - Athavale, Omkar N.; Di Natale, Madeleine R.; Avci, Recep; Clark, Alys R.; Furness, John B.; Cheng, Leo K.; Du, Peng (American journal of physiology: Gastrointestinal and liver physiology, 2024)
Mapping of rat gastric slow waves showed regional variations in their organization. In some subjects, separate wavefronts propagated near the lesser and greater curvatures with a loosely coupled region near the midline, between the wavefronts, having a varying slow-wave origin. Furthermore, simultaneous intracellular and extracellular recordings were concordant and independent of movement artifacts, indicating that extracellular recordings can be interpreted in terms of their intracellular counterparts when intracellular recording is not possible. Rhythmic electrical events, termed slow waves, govern the timing and amplitude of phasic contractions of the gastric musculature. Extracellular multielectrode measurement of gastric slow waves can be a biomarker for phenotypes of motility dysfunction. However, a gastric slow-wave conduction pathway for the rat, a common animal model, is unestablished. In this study, the validity of extracellular recording was demonstrated in vitro with simultaneous intracellular and extracellular recordings and by pharmacological inhibition of slow waves. The conduction pathway was determined by in vivo extracellular recordings while considering the effect of motion. Slow-wave characteristics [means (SD)] varied regionally having higher amplitude in the antrum than the distal corpus [1.03 (0.12) mV vs. 0.75 (0.31) mV; n = 7; P = 0.025 paired t test] and faster propagation near the greater curvature than the lesser curvature [1.00 (0.14) mm·s −1 vs. 0.74 (0.14) mm·s −1 ; n = 9 GC, 7 LC; P = 0.003 unpaired t test]. Notably, in some subjects, separate wavefronts propagated near the lesser and greater curvatures with a loosely coupled region occurring in the area near the distal corpus midline at the interface of the two wavefronts. This region had either the greater or lesser curvature wavefront propagating through it in a time-varying manner. The conduction pattern suggests that slow waves in the rat stomach form annular wavefronts in the antrum and not the corpus. This study has implications for interpretation of the relationship between slow waves, the interstitial cells of Cajal network structure, smooth muscles, and gastric motility. NEW & NOTEWORTHY Mapping of rat gastric slow waves showed regional variations in their organization. In some subjects, separate wavefronts propagated near the lesser and greater curvatures with a loosely coupled region near the midline, between the wavefronts, having a varying slow-wave origin. Furthermore, simultaneous intracellular and extracellular recordings were concordant and independent of movement artifacts, indicating that extracellular recordings can be interpreted in terms of their intracellular counterparts when intracellular recording is not possible.